IMPROVING CRITICAL THINKING SKILLS OF PG PAUD COLLEGE STUDENTS THROUGH SCIENTIFIC APPROACH TOWARDS NEUROSCIENCE IN TEACHING COURSE (A Classroom Action Research in PG PAUD Study Program of FKIP UNIB ) - Ardina, Mona; Agustina, Nesna (UNIB Press, 2017)
Abstract: This research aimed to improve critical thinking skills of college students through scientific approach in Learning Neuroscience. This research was classroom action research. This action research was carried out in 2 cycles. Every cycle consists of four steps: planning, implementing, observing, and reflecting. The collecting data technique used observation which was conducted at the first semester year 2017/2018. The subjects of this research were 36 college students of PG PAUD study programs of third semester year 2017/2018 who are taking Neuroscience course. The result showed that critical thinking skills in the first cycle has average 78,80, then in the second cycle improve into (average 84,50). The result indicated that scientific approach effectively improved critical thinking skills of college students’ in Neuroscience Course, thus graduated students of PG PAUD become professional teachers of PG PAUD in conducting teaching activity.Keywords: scientific approach, critical thinking